Channelopathy-related SCN10A gene variants predict cerebellar dysfunction in multiple sclerosis - Roostaei, Tina (Neurology, 2016)
OBJECTIVE: To determine the motor-behavioral and neural correlates of putative functional common variants in the sodium-channel Na(V)1.8 encoding gene (SCN10A) in vivo in patients with multiple sclerosis (MS). METHODS: We recruited 161 patients with relapsing-onset MS and 94 demographically comparable healthy participants. All patients with MS underwent structural MRI and clinical examinations (Expanded Disability Status Scale [EDSS] and Multiple Sclerosis Functional Composite [MSFC]). Whole-brain voxel-wise and cerebellar volumetry were performed to assess differences in regional brain volumes between genotype groups. Resting-state fMRI was acquired from 62 patients with MS to evaluate differences in cerebellar functional connectivity. All participants were genotyped for 4 potentially functional SCN10A polymorphisms. RESULTS: Two SCN10A polymorphisms in high linkage disequilibrium (r(2) = 0.95) showed significant association with MSFC performance in patients with MS (rs6795970: p = 6.2 × 10(−4); rs6801957: p = 0.0025). Patients with MS with rs6795970(AA) genotype performed significantly worse than rs6795970(G) carriers in MSFC (p = 1.8 × 10(−4)) and all of its subscores. This association was independent of EDSS and cerebellar atrophy. Although the genotype groups showed no difference in regional brain volumes, rs6795970(AA) carriers demonstrated significantly diminished cerebellar functional connectivity with the thalami and midbrain. No significant SCN10A–genotype effect was observed on MSFC performance in healthy participants. CONCLUSIONS: Our data suggest that SCN10A variation substantially influences functional status, including prominent effects on motor coordination in patients with MS. These findings were supported by the effects of this variant on a neural system important for motor coordination, namely cerebello-thalamic circuitry. Overall, our findings add to the emerging evidence that suggests that sodium channel Na(V)1.8 could serve as a target for future drug-based interventions to treat cerebellar dysfunction in MS.